Tooth Engineering: Searching for Dental Mesenchymal Cells Sources - Keller, Laetitia; Kuchler-Bopp, Sabine; Acuna Mendoza, Soledad; Poliard, Anne; Lesot, Hervé (Frontiers in Physiology, 2011)
The implantation of cultured re-associations between embryonic dental mesenchymal cells and epithelial cells from mouse molars at ED14 allowed making full teeth with crown, root, periodontal ligament fibers and bone. Although representing valuable tools to set up methodologies embryonic cells are not easily available. This work thus aimed to replace the embryonic cells by dental mesenchymal cell lines or cultured expanded embryonic cells, and to test their ability to mediate tooth development in vitro when re-associated with a competent dental epithelium. Histology, immunostaining and RT-PCR allowed getting complementary sets of results. Two different immortalized cell lines from ED18 dental mesenchyme failed in mediating tooth formation. The potentialities of embryonic dental mesenchymal cells decreased from ED14 to ED16 and were lost at ED18. This is likely related to a change in the mesenchymal cell phenotype and/or populations during development. Attempts to cultivate ED14 or ED16 embryonic dental mesenchymal cells prior to re-association led to the loss of their ability to support tooth development. This was accompanied by a down-regulation of Fgf3 transcription. Supplementation of the culture medium with FGF2 allowed restoring Fgf3 expression, but not the ability of mesenchymal cells to engage in tooth formation. Altogether, these observations suggest that a competent cell population exists in the dental mesenchyme at ED14, progressively decreases during development, and cannot as such be maintained in vitro. This study evidenced the need for specific conditions to maintain the ability of dental mesenchymal cells to initiate whole tooth formation, when re-associated with an odontogenic epithelium. Efforts to improve the culture conditions will have to be combined with attempts to characterize the competent cells within the dental mesenchyme.